Practical thinking while learning to program - novices' experiences and hands-on encounters - von Hausswolff, Kristina (Computer science education, 2022)
Research in programming education seems to show that hands-on writing at the keyboard is beneficial for learning, but we lack an explanation of why that is and an underlying theory to anchor that explanation. The first objective is to lay out a theoretical foundation for understanding the learning situation when novices first encounter programming in the computer lab. The second objective is to illustrate how this theoretical foundation can help give insight by applying it to an empirical study. Core concepts from Dewey's pragmatic theory are combined with the thinking of Deleuze and the later Wittgenstein to form a theoretical framework. The main empirical data is seven student interviews, which were analyzed using a qualitative content analysis method in two steps, first analyzing the stated content and second through the lens of the theoretical framework. Students' learning processes can be understood as 'come to agreement' and habitual actions when doing programming as 'practical thinking'. Programming education can be reframed beyond the theory-practice dichotomy already rejected by pragmatism. This may have an impact on both course design and assessment, in that knowledge and measurement of knowledge have to be re-evaluated in a pragmatic light.